Handbook of hospital infection control - Singhal, Sanjay (CBS Publishers & Distributors, 2013)
Emergence of difficult to treat infections caused by multidrug-resistant organisms has now made it essential that infection control policies should be prepared and followed. The Handbook therefore has been prepared by adopting current guidelines and policies regarding infection control from WHO COC APIC and other organizations. It focuses on the science of surveillance control and preventive management during episodes of endemic and epidemic outbreaks in the hospital. It will be useful for hospitals hospital administrators planners and managers as well as doctors nurses and medical students. It will help hospitals to plan infection control programs and policies and will be useful for clinicians by demystifying many myths about infection control. In addition the Handbook will be useful for nursing and medical students as infection control is already a part of nursing curriculum and is also being included in new MBBS curriculum being proposed by the Medical Council of India